‘To Know Whether the Patient Will Live or Die’ : A Medieval Medical Practice in Text and Diagram - Gottlieb, Sivan (Jewish Thought, 2025)
The desire to foresee the future, particularly the ability to predict death, has existed since antiquity. One method documented from the fourth century onward and found in numerous medieval manuscripts for predicting a patient’s fate is a computational tool known as the "Sphere of Life and Death." This tool combines text and diagram: the text provides instructions for the process, while the diagram is used for calculation and determining the outcome. In most cases, determining the patient’s fate involves combining values derived from the diagram, such as the patient’s name, the day of the week they fell ill, together with the day of the month they fell ill into a single sum. From this total, thirty is repeatedly subtracted until a number less than or equal to thirty remains. This final number is then located within the diagram, which indicates whether the patient will recover or die. This article explore the "Sphere of Life and Death" as it appears in Hebrew manuscripts dating from the 14th to the 19th centuries. It examines the tool’s adaptation into Hebrew, the integration of diverse traditions, and the modifications made to align with Hebrew language and culture, as well as later additions that suggest its practical application. The study focuses on the transfer of visual knowledge across cultures and the continuity of traditions, emphasizing the diagram’s essential and integral role within the "Sphere of Life and Death." The widespread presence of this tool across various cultures offers insight into its practical use and the beliefs associated with numerology, astrology, and divination.